2018
DOI: 10.1049/iet-map.2018.5373
|View full text |Cite
|
Sign up to set email alerts
|

Wideband tunable mid‐infrared cross‐polarisation converter using monolayered graphene‐based metasurface over a wide angle of incidence

Abstract: In this study, the authors have designed and proposed a monolayer graphene‐based metasurface, performing as a broadband polarisation converter over a wide angle of incidence. The unit cell of the metasurface consists of split ring generated over a perforated single layer of graphene grown over metal‐backed silicon dioxide. The structure converts incident linearly polarised wave into its cross‐polarised component over a wide bandwidth with peak polarisation conversion exhibits value to unity. The plane of polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…At present, the application of metamaterials is very extensive, and the technology combined with microfluidics has been applied to the detection of biomolecules [2,10,15,16]. These promising sensing tasks are typically achieved by measuring the difference in the resonance response of the metamaterial [17,18,19,20]. When the analysis sample is overlaid on top of the metamaterial, the altered resonance response is converted into a significant change in the transmitted or reflected signal in the response spectrum, and these changes can be detected directly [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the application of metamaterials is very extensive, and the technology combined with microfluidics has been applied to the detection of biomolecules [2,10,15,16]. These promising sensing tasks are typically achieved by measuring the difference in the resonance response of the metamaterial [17,18,19,20]. When the analysis sample is overlaid on top of the metamaterial, the altered resonance response is converted into a significant change in the transmitted or reflected signal in the response spectrum, and these changes can be detected directly [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent studies have indicated that the incorporation of lumped elements to enhance absorption bandwidth; however, they are quite challenging to realize in practice and contradict the ultra‐thin concept 9 . Recently, atomically‐thin two‐dimensional (2D) graphene‐based metasurfaces have attracted huge research attention owing to the controllability of graphene's conductivity, which helps in developing various metasurface related structures in THz frequency regions 10‐13 . In specific, graphene offers tunability in absorption bandwidth, where the conductivity of graphene has been modulated by controlling external parameters like chemical doping and mechanical straining 14‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to low profile and broad applications in microwave and optical fields several metasurface‐based designs have been studied comprising metasurface based slotted patch antenna, 6 metantenna, 7 tuneable metasurface, 8 compact metamaterial absorber 9 . Several metasurface designs for cross‐polarization conversion in terahertz domain are proposed in References 10‐13.…”
Section: Introductionmentioning
confidence: 99%